Specific COPII vesicles transport ER membranes to sites of autophagosome formation. (2nd January 2017) - Goder, Veit
ABSTRACT: The endoplasmic reticulum (ER) is considered a prominent membrane source for the formation of autophagosomes. Recent results from our laboratory revealed a cellular mechanism for the contribution of the ER to autophagosomes in yeast: membranes, together with unconventional membrane fusion machinery, are delivered to sites of autophagosome formation by specific coat protein complex II (COPII) vesicles.